Konstruksi Sosial Pekerja Perempuan dan Anak pada Industri Perikanan - Anggaunitakiranantika Anggaunitakiranantika (Sawwa: Jurnal Studi Gender, 2018)
Women worker and children employee on fishery industry aims to increase workforce participation around seashore edge beside budgeting pressure for labor cost. What is more necessary, the fishery industry is known as fishing manufacture in Pasuruan, tend to save their expenditure budget due to social subsidies to their employee. Thirty-four women who work at fishery industry was aged from 18 to 55 years old and the 8 children who engage with work was aged from 8 to 16 years old. There was wage gap between women worker and children worker. Gender dualism belongs to women worker and the children create social construction among local society in Pasuruan. Social construction happened because of dichotomy aspect. The first is working in the fishery industry was done with pride in breaking patriarchy rules, Secondly, they set to work for long-life family needed.